2006
DOI: 10.1542/peds.2006-0923
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Health Care Providers' Influence on Parents Who Have Concerns About Vaccine Safety and Vaccination Coverage

Abstract: Health care providers have a positive influence on parents to vaccinate their children, including parents who believe that vaccinations are unsafe. Physicians, nurses, and other health care professionals should increase their efforts to build honest and respectful relationships with parents, especially when parents express concerns about vaccine safety or have misconceptions about the benefits and risks of vaccinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
194
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(211 citation statements)
references
References 20 publications
11
194
0
6
Order By: Relevance
“…In a survey conducted in rural areas of Mozambique, authors reported a coverage rate of 72% for the complete schedule 15 . Coverage rates of nearly 70% were also reported in children enrolled in day care centers of Philadelphia, USA 16 , and in American children in general, between 2001-2002 17 . In some European countries or regions, coverage can be very low, as observed in Austria 18 and Germany 19 and in gipsy children from Alicante, Spain 20 .…”
Section: Discussionmentioning
confidence: 88%
“…In a survey conducted in rural areas of Mozambique, authors reported a coverage rate of 72% for the complete schedule 15 . Coverage rates of nearly 70% were also reported in children enrolled in day care centers of Philadelphia, USA 16 , and in American children in general, between 2001-2002 17 . In some European countries or regions, coverage can be very low, as observed in Austria 18 and Germany 19 and in gipsy children from Alicante, Spain 20 .…”
Section: Discussionmentioning
confidence: 88%
“…9,10 Even if the majority of cases of pandemic influenza A/H1N1 have been mild, severe disease has been reported in children, particularly in young children and those with high-risk medical conditions.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…Misperceptions of vaccine safety are a common contributor to low immunisation rates [2][3][4][5][6]. 60…”
Section: Introduction 57mentioning
confidence: 99%